SOSIALISASI â€œWASTE EDUCATIONâ€ DENGAN PENDEKATAN GAMIFIKASI - Ganing Irbah Al Lantip; Xenna Mutiara; Shinta Justicia Dellarohita; Destyana Eky Rahayu; Luke Arinda Febryola; Kusuma, Heri Septya (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Trash has become one of the urgent issues affecting the environment. Unfortunately, public awareness, particularly among students, about sorting waste according to its type is still not optimal. The â€œWaste Educationâ€ outreach activity aims to educate students of Universitas Pembangunan Nasional â€œVeteranâ€ Yogyakarta, especially the 2023 TK-B Class of the Department of Chemical Engineering, on the importance of proper waste management. This outreach activity was attended by 15 students. The socialization utilized a gamification approach in its implementation. The activity began with a presentation followed by playing a game from the website wordwall.com. This game was used to evaluate the students' understanding of the material presented earlier. After the gamification activity was completed, the team created a questionnaire on menti.com as a benchmark to measure the effectiveness of the event. Overall, participants gave positive feedback and found the â€œWaste Educationâ€ activity with the gamification method to be engaging and enjoyable.